DESIGN OF DRIVEN PILE AND DIAPHRAGM WALL FOR ITB INNOVATION PARK PROJECT IN SUMMARECON BANDUNG INTEGRATED AREA - Rajendra Dwiputranto, Ananda
The ITB Innovation Park project in the Summarecon Bandung Integrated Area consists of two main buildings and a two-level basement. Structurally, the buildings are constructed with a special moment-resisting frame system equipped with special structural shear walls (Dual System) to withstand seismic loads. This final project aims to design a foundation system capable of bearing the structure's load and a retaining wall system that ensures safety during basement excavation work. The design of the retaining wall aims to serve as an excavation protection system and will later become a permanent basement wall as well, reaching a depth of nine meters. Struts will be installed at each excavation stage to maintain excavation safety with a specific pre-tensioning force. The analysis is carried out both conventionally and using the MIDAS GTS NX application to simulate the excavation stages. The foundation system used is a pile foundation system unified by a raft. In determining the foundation's bearing capacity, soil parameters will be determined first using correlations from the available N-SPT data. Subsequently, the LPILE and GROUP applications are used to obtain the lateral capacity limit, moment, and load distribution from the column to each pile to check the safety factor requirements. This final check is done by modelling using the MIDAS GTS NX application to ensure the force distribution from the raft to the piles meets the requirements and to check for settlement.